Synthesis and Characterization of Iron(II) Carbonyl Complexes Related to Cluster-Free Hydrogenase - Long, Li; Wei, Zhenhong (Asian Journal of Chemistry, 2011)
Reactions of [Fe(CO)4I2] with one equivalent of PyCH2NHC2H4SNa (L1 – Na+) and PyCH2NH2 (L2) in THF separately gave rise to complexes [Fe(CO)2(L1)I] (1) and [Fe(CO)2(L2)I2] (2). Both the complexes show two strong carbonyl absorptions at 2027, 1974 cm-1 (1) and 2036, 1989 cm-1 (2), which are very close to that of cluster-free hydrogenase (Hmd).